Accuracy of Near Infrared-Guided Surgery in Morbidly Obese Subjects Undergoing Laparoscopic Cholecystectomy - Dip, Fernando; Nguyen, David; Montorfano, Lisandro; Noste, María Eugenia Szretter; Menzo, Emanuele Lo; Simpfendorfer, Conrad; Szomstein, Samuel; Rosenthal, Raul (Obesity surgery, 2016)
Background Fluorescence cholangiography represents an incisionless technique that can be applied during laparoscopic cholecystectomy to visualize bile ducts. Our objective was to evaluate and detect variances of fluorescence imaging in obese and non-obese patients. Methods Prospective patients were selected for laparoscopic cholecystectomies. Subjects were divided into groups based on their body mass index. Fluorescence imaging was applied preceding any dissection of extrahepatic ducts and again after dissection. Positive and negative identifications of biliary ducts were recorded. Results Seventy-one patients participated, with 53.5 % classified as obese. The cystic, hepatic, common bile duct, and accessory ducts were identified as follows: 100, 70.4, 87.3, and 7.0 % of patients, respectively. No differences in hepatic duct, common bile duct, and accessory duct visualization were detected in the obese and non-obese groups ( p value 0.09, 0.16, and 0.66, respectively). Conclusions Fluorescent cholangiography is a useful technique in the obese and non-obese population. Obesity does not affect fluorescence visualization of bile ducts.